Perubahan Asam Lemak Selama Penyimpanan Benih Kedelai (Glycine max L. Merr) dan Hubungannya dengan Viabilitas Benih - Aurellia Tatipata (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
This research was aimed to study fatty acid changes during soybean seed storage and to find method of soybean storage to maintain low free fatty acid content and high germination and vigor up to 6 months. The research was conducted at the Chemistry Laboratory of Mathematic and Natural Science Faculty, Pattimura University from May to December 2007. The experimental design used was factorial Experiment in Split- Split Plot Design, consisted of three factors, i.e. moisture content (8. 10 and 12%) as main plot, packaging materials (polyethylene, wheat and aluminium foil) as sub plot, storage period (0, 1, 2, 3, 4, 5, and 6 months) as sub-sub plot. Data were analyzed by analysis of variance and Duncan Multiple Range Test. Regression and correlation analysis were done to study the correlation between germination, vigor and free fatty acid. The results showed that fatty acid of soybean seed during storage at all levels of moisture content in wheat sack increased faster than that of other sacks. The free fatty acid content, germination and vigor of soybean seed stored in aluminium foil at all levels of moisture content slowly decreased within 6 months. Free fatty acid content had a significant negative correlation with germination and vigor. Keywords: soybean seed, fatty acid, storage, seed viability